Nano-pumice derived from pumice mine waste as a low-cost electrode catalyst for microbial fuel cell treating edible vegetable oil refinery wastewater for bioenergy generation and reuse - Fatemeh Eslami; Kamyar Yaghmaeian; Reza Shokoohi; Roohallah Sajjadipoya; Alireza Rahmani; Hedieh Askarpur; Abbas Norouzian Baghani; Hossein Jafari Mansoorian; Farshid jaberi Ansari (Heliyon)
This study aimed to assess nano-pumice (NP) from pumice mining waste as a local, cost-effective anode catalyst in microbial fuel cells (MFCs) for treating edible vegetable oil refinery wastewater (EVORW) and generating bioenergy. Pumice mining waste was converted into nano in three stages: crushing up to ≤3 cm, reducing the size of the previous step particles to 150 μm and converting the previous step particles to <100 nm. Nano-pumice prepared was coated on the carbon cloth (CC) to increase anode surface area of MFC. Two MFCs were utilized, with MFC-1 serving as a control and MFC-2 incorporating a CC electrode coated with nano-pumice. The surface morphology, elemental and chemical composition, and textural characterization of CC, pumice, NP, and CC coated with NP were analyzed using FE-SEM, EDX, XRF, and BET techniques. MFC-2 achieved a maximum power density of 30±4W/m³ at a current density of 55±5A/m³. The MFC-1 reached a maximum power density of 18±4W/m³ at a current density of 35±6A/m³. In MFC-2, the EVORW treatment achieved maximum removals of COD (94 ± 2 %), NH4+-N (85 ± 4 %), TP (76 ± 5 %), SO42− (68 ± 6 %), TSS (81 ± 2 %), and TDS (73 ± 1 %). MFC-1 achieved removal efficiencies of 66 ± 3 % for COD, 57 ± 6 % for NH4+-N, 48 ± 3 % for TP, 45 ± 3 % for SO42−, 65 ± 3 % for TSS, and 61 ± 1 % for TDS. MFC-2 power density rose significantly, reaching 61 ± 3 % (1.6 times) higher than MFC-1and it also demonstrated a superior ability to improve raw wastewater quality compared to MFC-1. The MFC with the CC/NP anode exhibited both excellent power production and high COD removal efficiency, making nano-pumice a suitable anode catalyst for MFC applications.